THE CLASSROOM MANAGEMENT PRACTICES OF YOUNG TEACHERS IN PUBLIC SECONDARY SCHOOLS IN ENUGU STATE, NIGERIA - Nnenna Amoke, Josephine; Ngozi Ezeaku, Felicia; Chukwuemeka-Nworu, Ijeoma Joyce; Amunabo Okwo, Fedrick; Enyi, Chinwe; Ndukwe Ukpai, Eke; Ngozi Nwafor, Bernadette; Chinwe Diara, Faith; Chinwe Omeke, Faith (International Journal of Psychosocial Rehabilitation, 2021)
The study examined the classroom management practices of young teachers in public secondary schools in Enugu State, Nigeria. Two research questions and one null hypothesis guided the study. The population of the study was all the 329 teachers of public secondary schools in the zone who has not taught for more than 4years, in 2016/2017 academic session. The sample used for the study was 120 teachers randomly selected from the three local government areas in the zone. A 20- item structured questionnaire developed by the researcher was used for data collection. The instrument was validated by two experts in Educational Administration and Planning and one from Measurement and Evaluation, all from University of Nigeria, Nsukka. The results were analysed using mean scores and standard deviations to answer the research questions, while t-test was used to test the hypothesis at 0.05 level of significance. The results showed that the performance of young teachers in classroom management in public secondary schools in Enugu State was low. It was also revealed that location of schools had no significant effect on performance of the young teachers. It was recommended among others that the Ministry of Education, Post Primary School Management Board and Administrators of schools should organize workshops, conferences and formal mentoring programmes for newly recruited teachers in the State.